2002
DOI: 10.1074/jbc.c200376200
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of Eukaryotic Initiation Factor (eIF) 4E Is Not Required for de Novo Protein Synthesis following Recovery from Hypertonic Stress in Human Kidney Cells

Abstract: Previous work has suggested that increased phosphorylation of eukaryotic initiation factor (eIF) 4E at Ser-209 in the C-terminal loop of the protein often correlates with increased translation rates. However, the functional consequences of phosphorylation have remained contentious with our understanding of the role of eIF4E phosphorylation in translational control far from complete. To investigate the role for eIF4E phosphorylation in de novo translation, we studied the recovery of human kidney cells from hype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
79
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 88 publications
(86 citation statements)
references
References 39 publications
6
79
1
Order By: Relevance
“…These data are quite surprising in light of previous reports where phosphorylation of Ser209 was most often correlated with cell growth in mammalian cells and was also shown to be critical for growth in Drosophila in toto (19). Although it was first reported that phosphorylation of eIF4E enhanced its affinity for the cap (25), reconstitution experiments of eIF4F complexes with purified molecules indicated that phosphorylation of eIF4E was not a prerequisite for complex formation with eIF4G (28), it was not required for translation (27), and it even reduced cap binding in vitro (43). Nevertheless, phosphorylation of Ser209 may still modulate a number of other protein-protein interactions that can affect the multiprotein 43S or 48S preinitiation complex, since the binding of eIF4E to eIF4G per se is known to change eIF4GI conformation, rendering it accessible to proteolytic cleavage (13,28).…”
Section: Discussioncontrasting
confidence: 46%
“…These data are quite surprising in light of previous reports where phosphorylation of Ser209 was most often correlated with cell growth in mammalian cells and was also shown to be critical for growth in Drosophila in toto (19). Although it was first reported that phosphorylation of eIF4E enhanced its affinity for the cap (25), reconstitution experiments of eIF4F complexes with purified molecules indicated that phosphorylation of eIF4E was not a prerequisite for complex formation with eIF4G (28), it was not required for translation (27), and it even reduced cap binding in vitro (43). Nevertheless, phosphorylation of Ser209 may still modulate a number of other protein-protein interactions that can affect the multiprotein 43S or 48S preinitiation complex, since the binding of eIF4E to eIF4G per se is known to change eIF4GI conformation, rendering it accessible to proteolytic cleavage (13,28).…”
Section: Discussioncontrasting
confidence: 46%
“…However, because the role of eIF-4E phosphorylation in translational control mechanisms is unclear (54 -56), and more targeted experimentation is required, such a suggestion would be premature. Perhaps paradoxically, phosphorylation of eIF4E is sometimes associated with a global inhibition of protein synthesis observed during cell stress or serum deprivation (57)(58)(59). This would provide a reasonable explanation for the conspicuous phosphorylation of eIF4E after 16 h in our quiescent cultures (1% serum) both in control and rhIL-17-treated wells (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Experiments that used polysomal mRNA profiling have suggested that eIF4E phosphorylation, per se, directly affects the translation efficiency of such genes (22), although the precise means by which phosphorylation regulates the translation of specific mRNAs is unclear because eIF4E phosphorylation is dispensable for global mRNA translation (30,46). That eIF4E phosphorylation is induced in untransformed cells under stress conditions (30,47,48) suggests that the physiologic MNKeIF4E connection has been usurped by cancer cells to compensate for and/or gain a growth advantage while under stress, including oncogene-induced senescence (49). Conversely, our finding that MNK-eIF4E activates self-renewal in BC leads us to speculate if equivalent pathways exist in normal stem cells to preserve selfrenewal capacity during physiologic stress.…”
Section: Discussionmentioning
confidence: 99%